S.2238 A Bill To Make Technical Corrections Relating To The Tax Reform Act Of 1986, And For Other Purposes (Tufts Archival Research Center, 2007)
Copy; Illegible/Difficult to Read; Amendment to S. 2238 proposed by Senator Ford (D-KY) making corrections to the Tax Reform Act of 1986. Mandates a study on the economic impact of smoking to be conducted by the Department of Treasury in conjunction with the Department of Health and Human Services. Dictates that the study include direct public health care costs, changes in incidence rates, the impact of cigarette taxes on smoking incidence, and the distributional effects of excise taxes.